Establishment and Development of Socio-Legal Work in the Children Primary Care in USSR - Leonid P. Chicherin; Valery Yu. Albitsky; Vladimir O. Shchepin; Anna A. Zagoruychenko ("Paediatrician" Publishers LLC, 2021)
Formative experience of establishment and development of legal support for maternity and childhood in USSR is considered over time and systematized. The role of measures taken by the socio-legal cabinet, as well as social patronage as the method of dynamic preventive identification of families with children who are in difficult circumstances. The author's vision on the accumulated experience significance in solving modern problems of protecting the child health and rights is presented.